Total-Factor Energy Efficiency and Productivity of ECOWAS States: A Slacks-Based Measure with Undesirable Outputs. Issue 1 (2nd January 2019) - Ohene-Asare, Kwaku; Turkson, Charles
ABSTRACT: Sub-Saharan Africa consumes far less energy per capita than world energy use per capita, yet energy efficiency is far lower in Africa. The Economic Community of West African States (ECOWAS) has been active in developing an energy efficiency policy aiming to improve efficiency levels in the region to be comparable to world levels. However, benchmarks used for the policy are based on traditional efficiency and intensity ratios. We examine the energy efficiency and energy productivity changes of ECOWAS members using nonparametric non-radial efficiency and dynamic productivity assessment techniques that take into consideration undesirable outputs. We find differences in the nature and levels of energy efficiency and sources of inefficiency among member states. We also observe that the major source of energy productivity growth in the region mainly relates to technical changes outside direct state control. There is a need for institutionalization of energy efficiency in the region by considering country-specific policies.